Perlindungan Data Pribadi Sebagai Bagian dari Hak Konstitusional Warga Negara dalam Sistem Informasi Partai Politik (SIPOL) - Raudatul Makfirah; Faisal Akbar Nasution; Abd Harris Nasution; Afnila Afnila (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This research aims to investigate the protection of personal data as a constitutional right of citizens based on Law Number 27 of 2022 concerning Personal Data Protection in Indonesia. In this study, the researcher identifies several main issues: the regulation of personal data protection in national law, personal data protection in the Political Party Information System (Sipol), and the resolution of disputes related to personal data protection by the Independent Election Commission (KIP) of Kabupaten Pidie. The research method used is normative and empirical with a legal regulation and case approach. Data collection was conducted through literature study and field research, followed by qualitative analysis to draw deductive conclusions. The research findings indicate that Law Number 27 of 2022 is the primary legal basis governing personal data protection, in accordance with the constitutional obligation stipulated in Article 28G paragraph (1) of the 1945 Constitution. The protection of personal data in Sipol includes oversight by the Election Supervisory Agency (Bawaslu), sanctions against the misuse of National Identification Numbers (NIK), and the importance of NIK verification. Dispute resolution is carried out through complaints from the public to KIP or Bawaslu, with individuals receiving a certificate regarding their membership status in Sipol. The conclusion of this research underscores the importance of law implementation in safeguarding citizens' personal data, particularly in political contexts such as Sipol. This protection not only ensures constitutional rights but also secures the integrity and security of personal data in the current digital era.